2019
DOI: 10.1111/1756-185x.13639
|View full text |Cite
|
Sign up to set email alerts
|

Plasma α‐L‐fucosidase‐1 in patients with Sjögren's syndrome and other rheumatic disorders

Abstract: Background Human α‐fucosidase (EC 3.2.1.51) is a hydrolase the importance of which has been increasing in the latest years. However, data about its plasma level in children with autoimmune disorders, particularly Sjögren's syndrome (SS), are lacking. In this study, the plasma activity of L‐α‐fucosidase‐1 (α‐L‐FUCA‐1) was assayed in hospitalized children and adults and its association with SS and other rheumatic disorders further evaluated. Methods In total 73 Hungarian hospitalized patients, 32 children (2.5‐1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Clinically, AFU is often served as a tumor marker in various cancers and its importance in the occurrence and progression of inflammatory and autoimmune diseases has been reviewed early ( 27 ). A research found that levels of AFU were significantly correlated to rheumatic diseases and the immune function of AFU may be a marker of rheumatism or chronic inflammatory manifestations ( 14 ). This research also pointed out that AFU activity in peripheral blood can be detected to further emphasize the relationship between glucose metabolism and immune response in RA patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically, AFU is often served as a tumor marker in various cancers and its importance in the occurrence and progression of inflammatory and autoimmune diseases has been reviewed early ( 27 ). A research found that levels of AFU were significantly correlated to rheumatic diseases and the immune function of AFU may be a marker of rheumatism or chronic inflammatory manifestations ( 14 ). This research also pointed out that AFU activity in peripheral blood can be detected to further emphasize the relationship between glucose metabolism and immune response in RA patients.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between AFU and autoimmune rheumatic disease was also discussed. For example, Endreffy et al reported that AFU was associated with chronic inflammatory pathologies in a pediatric cohort, suggesting that AFU is a biomarker of chronic inflammation and autoimmunity ( 13 ); moreover, alterations in plasma level of AFU were significantly associated with the development of Sjögren’s syndrome, and the preliminary result should encourage further research on AFU as a possible differential biomarker for Sjögren’s syndrome ( 14 ). A prior study proposed that the immune function of AFU may be a diagnostic marker of rheumatic disorders.…”
Section: Introductionmentioning
confidence: 99%
“…This leads to a neurovisceral condition known as fucosidosis, which is a rare lysosomal storage disorder inherited in an autosomal recessive pattern (Michalski and Klein 1999 ; Saleh-Gohari et al 2018 ). Recent works suggest that changes in the plasma level of FUCA1 can be associated with Sjögren’s syndrome, an autoimmune, chronic, and systemic disorder characterized by lymphocytic infiltration of the exocrine glands and a remarkable B-cell hyperactivity (Mavragani and Moutsopoulos 2014 ; Endreffy et al 2019 ). The presence of certain FUC, such as human plasma α-L-fucosidase (FUCA2), was found to be necessary for adhesion of Helicobacter pylori , particularly to gastric cancer and duodenal ulcer specific strains (Liu et al 2009 ; Miura et al 2019 ).…”
Section: First Part: Fucosidases As Tools and Targetsmentioning
confidence: 99%